Evaluating health-related quality of life in Ethiopia: systematic review and meta-analysis of EQ-5D-based studies - Tarekegn, Tenaw Baye; Gebrie, Desye; Kassaw, Abebe Tarekegn; Dagne Taye, Abebe; Girmaw, Fentaw; Ashagrie, Getachew (Frontiers in Epidemiology, 2024)
Background Health-related quality of life (HRQoL) is crucial for understanding how health conditions impact overall well-being. The EuroQol-5 Dimension (EQ-5D) is a widely used tool for measuring HRQoL across diseases. In Ethiopia, this tool has been employed to assess HRQoL across various healthcare settings. This study aims to summarize EQ-5D-derived health outcomes in Ethiopian populations and identify key determinants influencing these outcomes. Methods A systematic search of PubMed, Embase, and Scopus was conducted through May 2024, with no publication date restrictions, focusing on HRQoL and EQ-5D instruments in Ethiopian populations. Grey literature searches were also performed using Google's Advanced Search. Cross-sectional studies across various diseases were included. Data were extracted by two independent reviewers, and pooled mean EQ-5D utility and EQ-5D visual analog scale (EQ-VAS) scores were calculated using a random-effects model in STATA software version 17. Study quality was evaluated using the Agency for Healthcare Research and Quality (AHRQ) checklist, and heterogeneity was assessed using the I² statistic. Results Fourteen cross-sectional studies involving 5,639 patients from 2019 to 2024 in Ethiopia were analyzed. Health utility values varied across diseases, with pain/discomfort and anxiety/depression being the most commonly affected dimensions. The pooled EQ-5D utility for HIV patients was 0.88, and the EQ-VAS score was 76.59. For diabetes mellitus (DM) patients, the pooled utility was 0.78, and the EQ-VAS score was 69.36. For COVID-19 patients, the pooled utility was 0.86, and the EQ-VAS score was 74.56. Cancer patients had a pooled EQ-VAS score of 67.87. Conclusion The EQ-5D is a reliable tool for measuring HRQoL in Ethiopian patients across various diseases. The study's pooled EQ-5D scores provide valuable insights for future economic evaluations in the Ethiopian healthcare system. Systematic Review Registration https://doi.org/10.1136/bmjopen-2024-085354, PROSPERO (CRD42024505028).